Ownership structure, charateristic differences and the size of corporate board of commissioner: The case of Indonesia state-owned enterprises - Astami, Emita; Rusmin, Rusmin; Hartadi, B. (Virtus Interpress, 2011)
This study scrutinises the association between ownership identity and board size in a unique institutional setting: state-owned enterprises in Indonesia, a country incorporating a two-tier management structure. It investigates whether the ownership identity explains the size of the board of commissioners by using the year 2006 data set from 155 SOEs in Indonesia consisting of 112 of fully SOEs and 43 of partially- privatised SOEs. This study hypothesizes that SOEs with a higher level of private sector ownership will have a greater incentive to monitor the performance of executive management through board of commissioners than those SOEs that are fully owned by the state government. It finds that compared to those fully SOEs, the partially-privatised SOEs are likely to have more board of commissioners. Even though this result is not statistically significant and, therefore, the proposed hypothesis is not statistically supported, the regression statistical analysis reveals that control variables assist in explaining the size of board of commissioners. The size of the board of directors as a control variable is significantly associated with the size of the board of commissioners. Other control variables including size of the SOE as well as the return on equity measure moderately explain the size of the board of commissioners. The findings give insight to stakeholders such as regulators or the private sector investors interested in making investment decisions in Indonesia considering the ownership structure and the effect on the effectiveness of the board of commissioners.